LEARNING GUIDELINES OF INTEGRATION OF SOCIAL STUDIES CURRICULUM IN CHIANG MAI SPORTS SCHOOL - Nanchai, Sornwalai; Wannapaisan, Chetthapoom; Saenbutr, Sawaeng (Journal of MCU Nakhondhat, 2021)
The objectives of this article were to: 1) the generality of the Integrated learning management on social studies of Chiangmai Sports school students 2) the course of the integrated learning management on social studies of Chiangmai Sports school students. It is this survey research. The questionnaires had been applied to collect the survey data by the systematic sampling on 120 of Chiangmai Sports school students. Whereas the content analysis had been applied on the Interview data of 2 of the school principals. The results of the study are 1) The generality of the learning management of the Chiangmai Sports school consists of 3 appropriate aspects which have the percentage scores on the courses and teaching curriculums gain 56.34% ,the social studies teachers gain 89.21% and The evaluation of the social studies gains 71.24% 2) The course of the integrated learning management on social studies of Chiangmai Sports school based on the participating of the school principals and teachers on initializing the social studies courses of the Chiangmai Sports school. The solution of the inadequate studying is to have the extra class on Saturday and Sunday including the information advocacy on the smart classroom. The variety of evaluation had been applied to the students, for instance; by the activities, by observing on the individual groupworks or individual assignment.